PROP Nontaster Women Lose More Weight Following a Low‐Carbohydrate Versus a Low‐Fat Diet in a Randomized Controlled Trial. Issue 10 (25th August 2017) - Burgess, Brenda; Raynor, Hollie A.; Tepper, Beverly J.
Abstract : Objective: Taste blindness to 6‐n‐propylthiouracil (PROP) associates with increased fat preference and intake. No studies have matched a diet to a woman's PROP phenotype to improve weight loss. This study investigated (1) whether PROP nontaster (NT) women would lose more weight following a low‐carbohydrate (LC) diet than a low‐fat (LF) diet, and (2) whether PROP supertaster (ST) women would lose more weight following a LF diet than a LC diet. Methods: One hundred seven women (BMI = 34.8 ± 0.5 kg/m 2 ), classified as PROP NTs ( n  = 47) and STs ( n  = 60), were randomized to a LC or LF diet within a 6‐month lifestyle intervention. Assessments included 4‐day dietary recalls and biobehavioral and psychosocial questionnaires. Results: At 6 months, NTs lost more weight following the LC than the LF diet (−8.5 ± 0.5 kg vs. −6.6 ± 0.5 kg, P  = 0.008); there was no difference between STs following either diet (−8.8 ± 0.4 vs. −8.9 ± 0.5, P  = 0.35). Dietary self‐reports were unrelated to weight loss, and prescription of a LC diet associated with greater self‐efficacy. Conclusions: NT women lost more weight following the LC diet compared to the LF diet. Screening for PROP phenotype may help personalize diet therapy for NT women to optimize their short‐term weight loss.